URGENSI MEDIASI DALAM PERKARA PERCERAIAN DI PENGADILAN AGAMA - Umar Shofi; Indah Royani; Reny Alifah (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2023)
The Urgency of Mediation for Divorce Matters in the Religious Court. Dispute resolution through mediation (peace) has been known in Islam. Islam teaches that the parties to the dispute do peace. If peace is not found by the parties, the parties take on the role of the family to make peace. Herein precisely urgency mediation in Islam, that is, must give priority to the family. This is due to the families who are better informed and know intimately about the disputed issues in their lives. However, when the peace made by the family fails, then this decision will be submitted to the Religious. In divorce cases the function of an attempt to reconcile the duty of the judge as a mediator to be done based on Supreme Court Regulation No. 01 of 2008 on Mediation Procedures in Court. Therefore sought peace through mediation in the Religious that couples wishing to divorce the attack and reconciliation. Keywords: urgency, mediation in Islamic law, divorce case